Salicylic Acid as a Safe Plant Protector and Growth Regulator - Koo, Young Mo (Plant Pathol J, 2020)
Since salicylic acid (SA) was discovered as an elicitor of tobacco plants inducing the resistance against Tobacco mosaic virus (TMV) in 1979, increasing reports suggest that SA indeed is a key plant hormone regulating plant immunity. In addition, recent studies indicate that SA can regulate many different responses, such as tolerance to abiotic stress, plant growth and development, and soil microbiome. In this review, we focused on the recent findings on SA’s effects on resistance to biotic stresses in different plant-pathogen systems, tolerance to different abiotic stresses in different plants, plant growth and development, and soil microbiome. This allows us to discuss about the safe and practical use of SA as a plant defense activator and growth regulator. Crosstalk of SA with different plant hormones, such as abscisic acid, ethylene, jasmonic acid, and auxin in different stress and developmental conditions were also discussed.